Manhaj ibn Aqīl Fī al-Istishhād bi al-Amthāl al-Arabiyaah Fī Sharḥihin li Alfiah ibn Mālik - Han Xiao Hong; Ibrahim Tehhae (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This research aims to study the grammarians position on citing proverbs and other evidence that they relied on in grammatical complexity. The research in this study followed the descriptive analytical approach. This is to describe Ibn Aqil's approach in the issue of citing proverbs and to analyze that scientifically, as well as followed the historical approach in which the research helped in dealing with the events of grammar in history and grammarians and their effects. In the light of the information studied, the research reached the most important results: First: The study proved that Ibn Aqil’s commentary did not celebrate proverbs; Rather, it came in a few; This is due to his reliance - in most cases - on poetry, as is the custom of grammarians. Second: Ibn Aqil mentioned in his explanation of the millennium thirteen examples in grammatical issues, and he mentioned four proverbs in morphological issues. Third: Ibn Aqil followed the approach of the ancient grammarians in citing proverbs alongside other evidence from the Holy Qur’an, or poetry, which is the approach followed by grammarians.يهدف هذا البحث إلى دراسة موقف النحاة من الاستشهاد بالأمثال والأدلة الأخرى التي اعتمدوا عليها في التقعيد النحوي، كما يهدف إلى الوقوف على منهج ابن عقيل في الاستشهاد بالأمثال من خلال شرحه للألفية ابن مالك. واتبع البحث في هذه الدراسة المنهج الوصفي التحليلي؛ وذلك لوصف منهج ابن عقيل في قضية الاستشهاد بالأمثال وتحليل ذلك تحليلاً علميّاً، كما اتبع المنهج التاريخي الذي عاون به البحث في التعامل مع أحداث النحو في التاريخ والنحاة وآثارهم. وفي ضوء المعلومات المدروسة توصل البحث إلى نتائج أهمها: أولاً: أثبتت الدراسة أن شرح ابن عقيل لم يحتفل بالأمثال؛ بل جاءت فيه قليلة؛ ذلك لتعويله – في الأكثر- على الشعر كما هي عادة النحاة. ثانياً: أورد ابن عقيل في شرحه للألفية ثلاثة عشر مثلاً في القضايا النحوية، كما أورد أربعة أمثال في القضايا الصرفية، ثالثاً: سار ابن عقيل على نهج النحاة القدامى في الاستشهاد بالأمثال بجانب شواهد أخرى من القرآن الكريم، أو الشعر وهو المنهج المتبع لدى النحاة.